Improving child investigative interviewer performance through computer-based learning activities. (18th May 2016) - Powell, Martine B.; Guadagno, Belinda; Benson, Mairi
Abstract : The current study adopted a pre- versus post-training design and a standardised measure of performance to evaluate the effectiveness of a series of online computer-based learning activities designed to encourage open-ended question usage among investigative interviewers of children. Participants included 61 social workers, police and psychologists. The learning activities, organised into 12 modules of approximately 3 hours duration each, focused purely on the skill of eliciting a disclosure of sexual abuse and a narrative account of the offence from a young child. Results revealed a significant improvement in interview performance from pre-training to immediate post-training. For the 25 participants who also completed a follow-up assessment three to six months after completing the learning activities, performance was found to be maintained. The implications of these findings and directions for future research are discussed.